RECOVERY OF WASTE LEATHER FROM TANNERIES AS AGGREGATE IN COMPOSITE MATERIALS - POPIȚA, Gabriela-Emilia; ROȘU, Cristina; MANCIULA, Dorin; CORBU, Ofelia; POPOVICI, Antoanela (Studia Universitatis Babeș-Bolyai Ambientum, 2020)
This study proposes a recovery method for waste leather from tanneries, with high chromium content, by incorporating it into a composite material with cement matrix. The natural aggregates were substituted with CRT (cathode ray tubes) glass waste, with high lead content, originated from televisions and monitors dismantling. The material technological production flow was as follows: grinding skin (two types of skin: black and brown were used), mixing the ingredients after own recipes, pouring the mixture into molds, maturation, demoulding. The new material obtained was submitted to leachability tests to determine, using AAS (Atomic Absorption Spectrometry), the total chromium and lead concentration released from the material. The results showed that Cr and Pb were well retained in the cement matrix. The low levels of total Cr and Pb concentration were recorded at pH = 9-10 and pH = 12, for the composite containing black leather waste and and at pH = 2-3 and pH = 12 for the composite containing brown leather waste. Mechanical tests were also provided to evidence the mechanical properties of the composite. The new composite material obtained may be considered as construction material and can be classified in mortars class because of the size of the used aggregate (CRT glass waste).